Using intestinal flora to distinguish non-alcoholic steatohepatitis from non-alcoholic fatty liver. Issue 12 (December 2020) - Li, Chao; Cui, Lihong; Wang, Xiaohui; Yan, Zhihui; Wang, Shaoxin; Zheng, Yan
Objective: To explore specific flora in mouse models of non-alcoholic steatohepatitis (NASH) to improve NASH diagnostic protocols. Methods: Sixty mice were divided into normal diet (ND, 20 mice) and high-fat/high-sugar diet (HFSD) groups (40 mice). After 8 weeks of feeding, 10 mice in the ND group and 20 mice in the HFSD group were sacrificed to create the short-term ND and non-alcoholic fatty liver (NAFL) groups, respectively. After 16 weeks of feeding, the remaining mice were sacrificed to create the long-term ND and NASH groups, respectively. We then examined fecal flora, serum biochemical indices, and lipopolysaccharide and tumor necrosis factor-α levels and analyzed liver tissue. Results: The relative abundance of Lactobacillus, Desulfovibrio, Ruminiclostridium 9, and Turicibacter differed between NASH and NAFL mice, and the areas under the receiver operating characteristic curve of the four genera for diagnosing NASH were 0.705, 0.734, 0.737, and 0.937. The non-alcoholic fatty liver disease activity score was positively correlated with the relative abundance of Desulfovibrio (r = 0.353), Ruminiclostridium 9 (r = 0.431), and Turicibacter (r = 0.688). Conclusions: The relative abundance of Lactobacillus, Desulfovibrio, Ruminiclostridium, and Turicibacter may help distinguish NASH from NAFL.